The Link between Loneliness, Social Isolation, and Cardiovascular Disease - Khairina; Yusuf Ibrahim (Jurnal Psikiatri Surabaya)
Introduction: Cardiovascular disease (CVD) is a major cause of morbidity and mortality worldwide. Loneliness, a subjective feeling of social isolation, and social isolation, an objective lack of social connections, contribute to social vulnerability and physical frailty. Psychological factors and social support play important roles in CVD, affecting health behaviors and physiological mechanisms. This review aims to provide an understanding of how loneliness and social isolation impact CVD. Methods: A literature review was conducted to identify relevant studies investigating the association between loneliness, social isolation, and cardiovascular disease. Results: The findings indicate that social isolation and loneliness are significant risk factors for CVD, independent of other risk factors. The prevalence of loneliness has increased in modern society, affecting individuals of all ages. Loneliness and social isolation influence physiological processes such as activating the HPA axis, causing inflammation and alterations in immune function, and activating the sympathetic nervous system. These effects contribute to an increased risk of CVD, including elevated blood pressure, hypertension, atherosclerosis, and potential cardiac autonomic dysregulation. Conclusion: Loneliness and social isolation pose significant risks for cardiovascular disease (CVD), influencing physiological processes such as inflammation, immune function, and sympathetic nervous system activation. Understanding these relationships is crucial for developing effective strategies to prevent and manage CVD, emphasizing the importance of interventions targeting both psychological and physiological aspects of social well-being.